Clergy of the Russian Orthodox Church and West-Siberian farmers’ uprising of 1921 - Tsys Valeriy (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article deals with issues associated with participation of the Orthodox clergy in the West-Siberian Farmers’ Uprising of 1921, the largest anti-Communist popular uprising in the history of Soviet Russia and the USSR. It distinguishes main directions of the policy of rebels as to the religion and church, namely the employment of religious slogans in propaganda, granting back to the church certain functions in registering the population, return of religious attributes to state institutions and schools, permission to teach religion at schools, acknowledging the offi cial status of religious holidays, defending church property from Communist authorities and their supporters. The reason for the rebels’ support of the Russian Orthodox Church was their wish to win positive attitude of conservative farmers, to employ the ideological power of Orthodoxy, to restore the achievements of the February revolution that were eliminated by the Bolsheviks. The study shows types of participation of the clergy in the struggle against Bolsheviks. These are: appointing clergymen to military units, as it was common in the prerevolutionary army and the White units; calling clergymen to take part in important social and political events, such as openings of sessions of authorities of various levels, prayer services and sacred processions to gain victory, funerary ceremonies for the fallen in military action, fundraising for the People’s Army. It should be noted that the rebellion was supported by Nikolay (Pokrovskiy), archbishop of Tobolsk and Siberia. The article studies the consequences of supressing the rebellion. These were new repressions against the Russian Orthodox Church, including the arrest and murder of many clergymen.